Respective impact of bread structure and oral processing on dynamic texture perceptions through statistical multiblock analysis. (September 2016) - Jourdren, S.; Saint-Eve, A.; Panouillé, M.; Lejeune, P.; Déléris, I.; Souchon, I.
Abstract: Texture perception is a multidimensional and dynamic phenomenon resulting from both the initial structure of food and its breakdown during oral processing. The aim of this study is to identify the respective contribution of food and bolus properties to temporal changes in texture perceptions during bread consumption. For this purpose, the perception dynamics of three French baguettes with difstructures were assessed through Temporal Dominance of Sensations and Progressive Profiling. Samples of crumb with and without crust were tasted by trained panelists. The intensities of nine texture attributes were evaluated at three key stages of oral processing (10%, 40% and 100% of individual swallowing time) using the Progressive Profiling method. Six of them were related with a Multiblock Partial Least Squares (MB-PLS) regression to the initial bread properties and to some bolus properties measured at these three stages. The evolution during oral processing of some attributes such as "soft", "dry", "doughy" and "sticky" was more influenced by modifications of bolus properties than by the initial characteristics of the breads. Among bolus properties, the MB-PLS highlighted that the hydration and texture properties of the bolus had a greater impact on texture perceptions than bolus structure. The "aerated" perception was more affected by the crumb structure, while the "heterogeneousness" and the "crispiness" were more affected by the presence of crust. This study thus contributes to improving our understanding of dynamic texture perceptions through a statistical model that takes the physical properties of bread and bolus during oral processing into account. Graphical abstract: Highlights: Dynamic texture perceptions of three breads were assessed and compared through TDS and Progressive Profiling. Instrumental and sensory data were successfully linked through a regression model. Bolus properties had more impact on texture perceptions than the initial bread properties. Softness perception was mainly explained by bolus water content and hardness. Dryness perception was mainly explained by the water contents of both bolus and bread.